Предмет: Алгебра,
автор: IraVas2003
Докажите, что значение выражения (3x - 2)(2x - 3) - (3x + 2)(2x + 3) + 26x + 1 не зависит от значений x.
Ответы
Автор ответа:
0
раскрываем скобки:
6x^2-9x-4x+6-6x^2-9x-4x-6+26x+1=-13x-13x+26x+1=-26x+26+1=1 - х сократился, значит выражение от него не зависит
6x^2-9x-4x+6-6x^2-9x-4x-6+26x+1=-13x-13x+26x+1=-26x+26+1=1 - х сократился, значит выражение от него не зависит
Автор ответа:
0
Спасибо)
Похожие вопросы
Предмет: Математика,
автор: yliya29081984
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: niyazzhibek
Предмет: География,
автор: nastbaklanva2001
Предмет: Математика,
автор: MegaJambo